Believing and Willing Within the Correlation Between the Willing and the Willed in Blondel’s Action: A Reinterpretation of Immanentism and Transcendence - Francesco de Nigris (Religions)
The neglected correlation between willing and believing has prevented an understanding of the acting function of consciousness and the meaning of truth in Blondel’s philosophy of action, leading to its immanentist interpretation. To the extent that the intimate willing intention is revealed in the work that factually transcends the willed ends, in view of a single necessary end, thinking shows itself in ideas as principles of action that must come to be believed in their own willing and to make every act an act of faith.